Association of Circulating Magnesium Levels in Patients With Alzheimer's Disease From 1991 to 2021: A Systematic Review and Meta-Analysis - Du, Ke; Zheng, Xi; Ma, Zi-Tai; Lv, Jun-Ya; Jiang, Wen-Juan; Liu, Ming-Yan (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) remains a medical and social challenge worldwide. Magnesium (Mg) is one of the most frequently evaluated essential minerals with diverse biological functions in human body. However, the association between circulating Mg levels and AD remains controversial. We conducted a meta-analysis of 21 studies published between 1991 and 2021 to determine whether the Mg levels in the blood and cerebrospinal fluid (CSF) are abnormal in AD. Literatures were searched in PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), and Wanfang Data without language limitations. A pooled subject sample including 1,112 AD patients and 1,001 healthy controls (HCs) was available to assess Mg levels in serum and plasma; 284 AD patients and 117 HCs were included for Mg levels in CSF. It was found that serum and plasma levels of Mg were significantly reduced in AD patients compared with HCs (standardized mean difference [SMD] = −0.89; 95% confidence interval [CI] [−1.36, −0.43]; P = 0.000). There was statistically non-significant for Mg level in CSF between AD and HCs, whereas a decreased tendency were detected (SMD = −0.16; 95% CI [−0.50, 0.18]; P = 0.364). .In addition, when we analyzed the Mg levels of serum, plasma and CSF together, the circulating Mg levels in AD patients was significantly lower (SMD = −0.74, 95% CI [−1.13; −0.35]; P = 0.000). These results indicate that Mg deficiency may be a risk factor of AD and Mg supplementation may be a potentially valuable adjunctive treatment for AD. Systematic Review Registration:www.crd.york.ac.uk/PROSPERO/, registration number CRD42021254557.